A Replication Study of Waiting for Service: The Relationship Between Delays and Service Evaluations - Wang, Xiaolin (Auckland University of Technology, 2006)
Delays in service are becoming a pervasive phenomenon which occurs in many service encounters. In the last ten years, a great number of studies have focused on the effects of delays on service evaluations. The purpose of this study, considered a close replication of a study of Shirley Taylor (1994), is to examine the relationship between delays and overall service evaluations and design the survey questionnaires for delayed airline passengers. This particular study reviewed and examined the relationship between delays and service evaluations by assessing the effects of delay duration, attribution for the delays, and the degree of filled time on affective reactions to the delay. It revealed that delays do affect the overall evaluations of service, mediated by the negative emotional reactions of anger and uncertainty, and influence the complaint action and repurchase intentions of consumers. At the same time, a consumer’s perceived degree of controllability of a service provider, and the level of filled time was found to indirectly influence the service evaluations through the mediating role of emotional reactions. Using information published in the marketing literature, two questionnaires have been designed and pre-tested for use in further studies.
Keywords: Airlines - customer services; Consumer satisfaction - evaluation; Customer relations; Surveys; Taylor, Shirley F.